Correlation between Temperature Activation of Charge‐Carrier Generation Efficiency and Hole Mobility in Small‐Molecule Donor Materials. Issue 6 (1st April 2014) - Koerner, Christian; Hein, Moritz Philipp; Kažukauskas, Vaidotas; Sakavičius, Andrius; Janonis, Vytautas; Fitzner, Roland; Bäuerle, Peter; Leo, Karl; Riede , Moritz
Abstract In organic solar cells, free charge carriers are generated at the interface between an electron‐donating and an electron‐accepting material. The detailed mechanisms of the generation of free charge carriers are still under discussion. In this work, we investigate the influence of temperature on the generation efficiency of free charge carriers in blends of dicyanovinyl substituted oligothiophene (DCVnT) molecules and C60 by quasi‐steady‐state photoinduced absorption (PIA) measurements. The observed positive temperature dependence of charge‐carrier generation can be directly correlated to the charge‐transport behavior. The determined activation energy scales inversely with the hole mobility for all investigated DCVnT derivatives, suggesting higher dissociation probability of bound interfacial charge pairs at high mobility. Furthermore, the energetic disorder parameter, σ, determined by CELIV (charge extraction by linearly increasing voltage) measurements for a DCV6T derivative, matches the activation energy from the PIA measurements. In conclusion, these results underline the need for high‐mobility donor materials for optimal charge‐pair dissociation in organic solar cells.